2020
DOI: 10.1002/chem.201904456
|View full text |Cite
|
Sign up to set email alerts
|

Untying the Photophysics of Quinolinium‐Based Molecular Knots and Links

Abstract: Complex molecular knots and links are still difficult to synthesize and the properties arising from their topology are mostly unknown. Here, we report on ac omparativep hotophysical study carried out on af amily of closely related quinolinium-based knots and links to determine the impact exertedby topology on the molecularb ackbone. Our results indicatet hat topology has an egligible influence on the behavior of loosely braided molecules, which mostly behave like their unbraided equivalents. On the other hand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 77 publications
0
14
0
1
Order By: Relevance
“…This acid/base switching behavior inspired Cougnon, Kumpulainen, and co‐workers to exploit the trefoil knot 31 6+ and the Solomon link 29 8+ in the development of molecular switches . As discussed earlier, the protonated forms of 31 6+ and Solomon link 29 8+ are able to recognize two Br − anions and four water molecules, respectively, through the formation of hydrogen bonds between these guests and the hydrazone NH protons.…”
Section: Self‐assembly Based On Acylhydrazone Formation In Watermentioning
confidence: 85%
“…This acid/base switching behavior inspired Cougnon, Kumpulainen, and co‐workers to exploit the trefoil knot 31 6+ and the Solomon link 29 8+ in the development of molecular switches . As discussed earlier, the protonated forms of 31 6+ and Solomon link 29 8+ are able to recognize two Br − anions and four water molecules, respectively, through the formation of hydrogen bonds between these guests and the hydrazone NH protons.…”
Section: Self‐assembly Based On Acylhydrazone Formation In Watermentioning
confidence: 85%
“…The nonbasic anions (Br − , NO 3 − , ClO 4 − ) did not change the absorption spectra, while the basic anions led to an increasing peak at 420 nm with increasing PL intensity ( Figures S7 and S8). According to the previous literature, the pK a of acyl hydrazone N-H ranges from 8.8 to 11.3 in aqueous solution [62]. The pH value of bQH solution (5.0 × 10 −6 M in DMSO) was measured to be 8.0 using a pH meter.…”
Section: Resultsmentioning
confidence: 99%
“…Tying strands, which will result in an increase in local bulk, while introducing topological chirality into molecules will become a center stage in chemistry. Recently, empirical investigations 45,209,215,247 have been conducted to unravel how tightness and chiral expression can be influenced by the topology of a molecule. Leigh 46 has shown that the chiral expression in a nanoscale knot can invert reversibly the chiral organization of cholesteric liquid crystals on the centimeter scale, i.e., chiral amplification can span over seven orders of scalar magnitude.…”
Section: Discussionmentioning
confidence: 99%